Investigation of the Compressive Strength of Fly Ash–based Geopolymer Concrete cured by Oven and Microwave Radiation - Minh, Tran Nhat; Nguyen, Tan Khoa; Nguyen, Ninh Thuy; Nguyen, Tan Hung; Le, Anh Tuan (Engineering, Technology & Applied Science Research, 2025)
This study investigates the influence of three different curing methods -oven, microwave, and hybrid microwave–oven- on the compressive strength of Fly Ash (FA)-based geopolymer concrete. Five mixtures with an Alkaline Liquid (AL) to FA ratio varying from 0.6 to 1.0, combined with different curing conditions, were tested to evaluate the highest compressive strength values. The results revealed that the maximum compressive strength was observed at 30.2 MPa for oven-curing at 80 ℃ for 16 hours, 13.7 MPa for microwave curing at 400 W for 10 minutes, and 33.1 MPa for hybrid curing (microwave at 400 W for 10 minutes) followed by oven at 80 ℃ for 8 hours. These findings indicate that the hybrid curing method is an optimal solution, developing higher compressive strength in a shorter time compared to traditional curing methods.